Perancangan Perkuliahan Fisika Berbasis KKNI Yang Mendukung Kompetensi Lulusan Program Studi Teknik Industri - Tiara Nurhuda (Sainteks: Jurnal Sain dan Teknik, 2020)
The increasing number of buying and selling transactions through e-marketplaces today causes the need for a model that is able to measure the extent of acceptance of e-marketplace applications. The existence of a model of measuring e-marketplace acceptance will greatly help business people in that field in order to improve the performance of the service products it offers, which in this study is Lazada. This research was conducted to find out how far the user acceptance of Lazada e-marketplace applications using the Technology Acceptance Model (TAM). The approach on this research is using quantitative approach with a survey method. Data collection techniques were carried out using questionnaires that were randomly distributed to Lazada e-marketplace users. The data analysis method used is descriptive analysis using multiple linear regression data analysis techniques. The results showed that content richness, security and perceived ease of use variables had a significant effect on the perceived of usefulness variable, security variables had a significant effect on perceived usefulness variables, perceived usefulness variables, perceived ease of use and security had a significant effect on the variables customers intention to use.